Deliberative democracy becomes institutional democracy: Is it dangerous to give power to the people? Comments on Vilhjálmur Árnason’s paper "Power to the People?" - Ólafsson, Jón (Stjórnsýslustofnun, 2014)
The paper is a response to Vilhjálmur Árnason’s writings on democracy, in particular his paper "Power to the People? Weaknesses and challenges of Icelandic democracy in the wake and aftermath of the Crisis." It is argued that Árnason’s criticism of democratic experiments in Iceland after the economic crisis of 2008 imply doubts about democracy and that the form of democracy that Árnason favors in fact means that good governance is seen as more important than democracy. The paper discusses political deliberation, participation and an independent public sphere that can accommodate both deliberative democracy and independent media. It is maintained that it may be difficult or even impossible to evaluate from outside the extent to which private interest, oratorial contests and political bargaining dominate the political field. General moral norms are of little help in evaluating political discourse. Further the paper argues that experiments in Iceland such as referenda, national fora and the Constitutional Council have provided valuable experiences from which it is important to learn rather than simply claim that serious mistakes were made in their organization and implementation as Árnason claims. Finally it is pointed out that doubts about direct democracy have not been answered in a satisfactory way and that in order to strengthen the argument for direct democracy a few key doubts must be dealt with more convincingly than one has yet seen in the literature. Greinin er viðbrögð við skrifum Vilhjálms Árnasonar um lýðræði, einkum grein hans "Valdið fært til fólksins? Veikleikar og verkefni íslensks lýðræðis í aðdraganda og eftirmála hrunsins." Því er haldið fram að gagnrýni Vilhjálms á lýðræðistilraunir á Íslandi í kjölfar hrunsins 2008 tjái efasemdir um lýðræði og að það form lýðræðis sem Vilhjámur telur heppilegast feli í raun í sér áherslu á vandaða stjórnsýslu á kostnað lýðræðis. Fjallað er um pólitískar umræður, þátttöku og óháðan vettvang almannahagsmuna sem geti rúmað bæði rökræðulýðræði og sjálfstæða ...